Albania Credit Guarantee Scheme Assessment - World Bank (World Bank, Washington, DC, 2020)
Micro, small, and medium enterprises (MSMEs) in Albania are significant contributors to the economy. In 2018, according to the Albanian Institute of Statistics (INSTAT), 99.8 percent of active enterprises were MSMEs, employing 79.8 percent of the workforce and realizing around 69 percent of value added. At the same time, the MSME sector is generally characterized by high informality (especially in agriculture), limited availability of collateral, and low levels of financial capability. Limited access to finance, particularly bank credit, poses a challenge for MSMEs in Albania. MSMEs can only reach their full potential if they obtain the finance necessary to start, sustain, and grow their business. Albania’s financial sector ranks at 102nd place out of 141 countries in the World Economic Forum 2019 Global Competitiveness Report. Credit to the domestic private sector represents only 33 percent of gross domestic product (GDP) compared to above 50 percent in regional peers, reflecting very low levels of financial intermediation. MSMEs – the backbone of the Albanian economy – face significant constraints in accessing finance, with 16 percent of small and 34 percent of medium-sized enterprises reporting access to finance as a major constraint in Albania. The overall MSME finance gap in Albania is estimated at 9 percent of GDP. The Albanian banking sector is extremely liquid and prevailing interest rates are low; however, Albanian banks are reluctant to lend to MSMEs as they perceive the sector as risky and there is a limited secondary market for movable and immovable collateral. Improving access to finance for MSMEs in the country must be tackled in a holistic and strategic manner, addressing supply, demand, and enabling environment aspects.